A cross-sectional study for the assessment of sensitization to indoor and fungal allergens in stable persistent asthma and its association with serum immunoglobulin E - Rajesh K. Palvai; Karthik Velimala; Nalini Ghanate; Anvesha Tummala; G. Sravan Kumar; T. Pramod Kumar (MRIMS Journal of Health Sciences)
Background: Bronchial asthma is characterized by bronchoconstriction and hyperresponsiveness to allergens. The management of asthma includes bronchodilator therapy and identification of allergens to limit exposure. There is a need to screen for sensitization to reduce exacerbations and achieving symptom control in asthmatics. Objective: To assess sensitization to indoor allergens and fungi in stable persistent asthmatics. Materials and Methods: This was a cross sectional study conducted among the patients with persistent bronchial asthma attending out-patient,who consented to procedure were randomly selected. One hundred of these patients who satisfied the inclusion and exclusion criteria were questioned about allergen exposure and tested with skin prick test (SPT). Results: In this study, Out of 100 patients tested, sensitization was noted among 80% of patients to 26 different allergens. Sixty-five percent of patients in the study group tested positive by SPT for more than one allergen. 53% were sensitized to Dermatophagoides pteronyssinus, 52% to Dermatophagoides farinae, 35% to Blomia tropicalis, and 26% to cockroach, 17% to house dust, 16% to Aspergillus fumigatus, 14% to Candida, 6% to Penicillium and Alternaria, 5% to Aspergillus Niger and Aspergillus Flavus, and 4% to Cladosporium. In allergen sensitized individuals, elevated serum immunoglobulin E (IgE) values were associated with severity of airway obstruction (prebronchodilator FEV1). Conclusion: Asthmatics with poor symptom control showed high sensitization to indoor allergens with house dust mites being most common. Skin testing should be preferred to serum IgE as there was considerable overlap between mono and nonsensitized individuals.